The Time Course of Color- and Luminance-Based Salience Effects - Dombrowe, Isabel C.; Olivers, Christian N.; Donk, Mieke (Frontiers in Psychology, 2010)
Salient objects in the visual field attract our attention. Recent work in the orientation domain has shown that the effects of the relative salience of two singleton elements on covert visual attention disappear over time. The present study aims to investigate how salience derived from color and luminance differences affects covert selection. In two experiments, observers indicated the location of a probe which was presented at different stimulus-onset-asynchronies after the presentation of a singleton display containing a homogeneous array of oriented lines and two distinct color singletons (Experiment 1) or luminance singletons (Experiment 2). The results show that relative singleton salience from luminance and color differences, just as from orientation differences, affects covert visual attention in a brief time span after stimulus onset. The mere presence of an object, however, can affect covert attention for a longer time span regardless of salience.